Groundwater connectivity controls peat burn severity in the boreal plains. Issue 4 (30th July 2015) - Hokanson, K. J.; Lukenbach, M. C.; Devito, K. J.; Kettridge, N.; Petrone, R. M.; Waddington, J. M.
Abstract: Wildfire is the largest disturbance affecting peatland ecosystems and can typically result in the combustion of 2–3 kg C m −2 of near‐surface peat. We hypothesized that organic soil burn severity, as well as the associated carbon emissions, varies significantly as a function of hydrogeological setting due to groundwater impacts on peat bulk density and moisture content. We measured depth of burn (DOB) in three peatlands located along a hydrogeological and topographic gradient in Alberta's Boreal Plains. Peatland margins across all hydrogeological settings burned significantly deeper (0.245 ± 0.018 m) than peatland middles (0.057 ± 0.002 m). Further, hydrogeological setting strongly impacted DOB. A bog with an ephemeral groundwater connection in a coarse‐textured glaciofluvial outwash experienced the greatest DOB at its margins (0.514 ± 0.018 m) due to large water table fluctuations, while a low‐lying oligotrophic groundwater flow‐through bog in a coarse‐textured glaciofluvial outwash experienced limited water table fluctuations and had the lowest margin burn severity (0.072 ± 0.002 m). In an expansive peatland in a lacustrine clay plain, DOB at the margins bordering an isolated domed bog portion (0.186 ± 0.003 m, range: 0.0–0.748 m) was considerably greater than the DOB observed at fen margins with a longer groundwater flow path (<0.05 m). Our research indicates that groundwater connectivity can have a dominant control on soil carbon combustion across and within hydrogeological settings. We suggest that hydrogeological setting be used to identify potential deep burning 'hotspots' on the landscape to increase the efficacy of wildfire management and mitigation strategies. Copyright © 2015 John Wiley & Sons, Ltd.